Design and Operational Effect Analysis of the Consumption Early Warning Function of the New Energy Cloud Platform - Li Nana; Xie Guohui; Qi Caijuan; Ma Yanxia; Shan Yu (E3S Web of Conferences, 2022)
The New Energy Cloud platform provides users with efficient, fair, just, and quality services, and optimizes the business environment in the new energy field. It is of immense significance in promoting national energy transformation, accelerating power system reform, and building the Energy Internet, and can effectively support the construction of energy big data centers, form an ecosystem of the energy industry, drive the intelligent manufacturing of equipment, and boost economic growth. We studied the design of the consumption early warning function of the consumption computing sub-platform of the New Energy Cloud, and propose the analysis indicators and consumption early warning methods and the operational benefit analysis process of the consumption early warning function. Finally, we demonstrate the results of the consumption early warning function of the New Energy Cloud platform and analyze the operational effect of the consumption early warning function.